2018
DOI: 10.1075/jlp.18014.sto
|View full text |Cite
|
Sign up to set email alerts
|

Put your “big girl” voice on

Abstract: Heckles are an illegitimate, yet common way of commenting directly and immediately on what is being said at the lectern. However, (non-)verbal interjections can also be used to disconcert the speaker, thus scoring points within the parliamentary arena. In these cases, female delegates are often confronted with discriminatory remarks and comments that border on sexism and even misogyny. Based on the extensive literature on gender and discourse, the following paper will focus on gender-related heckles and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…For example, Georgalidou (2017) found that women are subject to sexist aggression and derogative forms of addresses in the Greek parliament. Likewise, Stopfner (2018) shows that in the Canadian, German, and British House of Commons, women are frequently subject to interruptions targeting their appearance, competence, gender roles, or personal traits. Collier and Raney (2018) analyze the lower Houses in Australia, the United Kingdom, and Canada and find that women are subject to sexist heckles, taunts, and shouting while Erikson and Josefsson (2018) find that women report being frequently interrupted in the Swedish parliament.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Georgalidou (2017) found that women are subject to sexist aggression and derogative forms of addresses in the Greek parliament. Likewise, Stopfner (2018) shows that in the Canadian, German, and British House of Commons, women are frequently subject to interruptions targeting their appearance, competence, gender roles, or personal traits. Collier and Raney (2018) analyze the lower Houses in Australia, the United Kingdom, and Canada and find that women are subject to sexist heckles, taunts, and shouting while Erikson and Josefsson (2018) find that women report being frequently interrupted in the Swedish parliament.…”
Section: Introductionmentioning
confidence: 99%